Appraisal of Heavy Metals in Some Fruits Sold in Effurun Market - Matthew Eturhobore Adu; Maxwell Momah (West African Journal of Allied Health Sciences, 2026)
Background: Heavy metal contamination of edible food has become rampant in our society and this has led to increase in the occurrence of terminal diseases in the society. Fruits are cultivated, harvested and sold without cooking thereby protecting the nutrients in them. Contamination of fruits by heavy metals have been reported in some parts of Nigeria. Aim: Hence, this study aims to appraise the heavy metals in some fruits sold in Effurun market. Methods: Five edible fruits of Orange (Citrus sinensis), Watermelon (Citrullus lanatus), Cucumber (Cucumis sativus), Pineapple (Ananas comosus) and Banana (Musa sapientum) were digested and evaluated for the presence of heavy metals using atomic absorption spectrophotometer (AAS). Results: The study revealed varying concentrations of heavy metals among the fruit samples. Copper, Chromium and Cadmium showed relatively higher concentrations compared to the permissible limits in all the fruits evaluated, while nickel was higher in C. sativus and remain within permissible limits in other fruits. Cobalt, manganese, zinc and lead were all within the permissible limits established by the World Health Organization and Food and Agriculture Organization for all the fruits examined. Conclusion: The differences in metal concentrations may be attributed to environmental exposure, transportation, storage conditions, and contamination from agricultural inputs. Although some fruits remained within acceptable safety limits, continuous consumption of contaminated fruits may predispose consumers to bioaccumulation and associated health risks such as nephrotoxicity, hepatotoxicity, neurological disorders, and carcinogenic effects. Regular monitoring of heavy metal contamination in fruits sold in local markets is essential to safeguard public health. Implementation of stricter environmental regulations, improved agricultural practices, and periodic food safety surveillance are recommended to minimize heavy metal exposure through fruit consumption.